Factors affecting inflation in Malaysia / Zarifah Abd Malik - Abd Malik, Zarifah (Faculty of Business and Management, 2019)
The objective of this study is to conduct the relationship between Inflation Rate with macroeconomic variables or indicator as an independent variable that would be affecting to the dependent variables. The selected macroeconomic variables or the independent variables used are money supply, exchange rate, interest rate, gross domestic product and unemployment rate for period from 2004 to 2016 quarterly, which the total number of observation is 52, while the dependent variables is inflation rate. The relationship is examined by undertaking regression analysis using time series data that collected from World Bank Database. Both Single Linear Regression and Multiple Linear Regression are used to identify the relationship between dependent and independent variables. From the result, the study shows that money supply, exchange rate and gross domestic product has negative significant relationship toward inflation. Interest rate has positive significant relationship meanwhile; unemployment has negative insignificant relationship toward inflation. This indicates that interest rate give impacts towards inflation while money supply, exchange rate, gross domestic product and unemployment rate does not give impact to inflation rate in Malaysia. The relationship discovered should be useful for public, industries and policy makers as well.